Enlargement of polytopic terminal region in NMPC by interpolation and partial invariance - Cannon, M; Kouvaritakis, B; Deshmukh, V (2004)
This paper uses the concept of partial invariance to derive a sequence of linear programs in order to maximize offline the volume of an invariant polytopic set with an arbitrary predefined number of vertices subject to a bound on closed-loop performance. Interpolation techniques are used to determine a nonlinear control law which is optimal with respect to a closed-loop cost bound through the on-line solution of a linear program. The invariant polytope is also used to define a receding horizon control law through an appropriate terminal constraint and cost. © 2003 Elsevier Ltd. All rights reserved.